A United Kingdom national survey of trends in ectopic pregnancy management. (August 2014) - Taheri, M.; Bharathan, R.; Subramaniam, A.; Kelly, T.
Abstract Our national survey demonstrates increased use of medical and laparoscopic management of ectopic pregnancy in the UK. In the UK in 2000, 35% of cases were managed by laparoscopy, 63% by laparotomy and 1% with medication. A recent review in the USA revealed increasing rates of medical management and decreasing rates of laparotomy; a trend driven by both cost-effectiveness and patient choice. A total of 119 early pregnancy units were surveyed regarding the nature and management of the three most recent cases of ectopic pregnancy; in addition, feasibility of training residents was also requested. Participants reported on 124 cases with a median of five cases per month per department. A total of 57% of cases were managed laparoscopically, 31% medically, 5% by laparotomy and 6% conservatively. Out of 44 centres, 29 have the facilities for training in both intermediate laparoscopic surgery and early pregnancy ultrasound.